Impact of COVID-19 on diets of poor consumers in Africa: Evidence from the slums of Nairobi, Kenya. - Chege, Christine G. Kiria; Onyango, Kevin; Kabach, Joram; Lundy, Mark M. (International Center for Tropical Agriculture, 2020)
The COVID-19 pandemic has disrupted food systems worldwide, and this is likely to have negative implications for food and nutrition security. The vulnerable poor, especially those in the urban areas, are likely to feel a bigger impact. More than half of Africa's urban population lives in slums. Little is known about the impact of the current pandemic on their consumption behavior and diets. This study analyzes effects of the COVID-19 pandemic on consumption of nutritious foods (including fresh fruits and vegetables and animal source foods) and diets of poor slumdwellers and middle-income non-slum dwellers in Nairobi, Kenya, using primary data collected from 2,465 households between April and May 2020. Food (in)security assessment and consumption behavior questions are asked to capture before and during pandemic using recall. In addition, household dietary diversity scores are calculated based on 7-day food consumption recalls. Both descriptive and econometric regression analyses are conducted. Households in the slums are affected more than the non-slum middle-income households. More than 40% of slum households do not have jobs, their average monthly household income is very low, at USD78. About 90% of households in the slums reported dire food insecurity situations. They were not able to eat the kind of foods they preferred, they ate a limited variety of foods, a smaller meal than they felt they needed and fewer number of meals in a day. Slum households have a lower dietary diversity score (4 out of 9) compared to the non-slum (5 out of 9). In addition, slum dwellers show larger negative effects on consumption of nutritious foods especially fresh fruit and vegetables and animal source foods. Several factors associated with quality food consumption during the pandemic period are highlighted. Mitigation measures should pay close attention to slums as they are deeply impacted by the pandemic. In addition, policy design and implementation should be inclusive of the vulnerable poor consumers in the slums.